Muscle Contractile Properties Measured at Submaximal Electrical Amplitudes and Not at Supramaximal Amplitudes Are Associated with Repeated Sprint Performance and Fatigue Markers - Alejandro Muñoz-López (MDPI AG, 2021)
Background: The present study analyzes the associations between the muscle contractile properties (MCP) measured at different neuromuscular electrical stimulation amplitudes (NMESa) and the performance or transient fatigue after a bout of repeated sprints. Methods: Seventeen physically active male subjects performed six repeated sprints of 30 m with 30 s of passive recovery. Capillary blood creatine kinase (CK) concentration, knee extension or flexion isometric peak torque, tensiomyography, and repeated sprint performance were assessed. Results: Muscle displacement and contraction time were different in relation to the NMESa used in the rectus femoris and biceps femoris muscles. At rest, significant (p < 0.05) associations were found between muscle displacement and the loss of time in the repeated sprints (sprint performance) at 20 or 40 mA in the rectus femoris. At post +24 h or +48 h, the highest significant associations were found between the muscle displacement or the contraction time and CK or peak torques also at submaximal amplitudes (20 mA). The NMESa which elicits the peak muscle displacement showed lack of practical significance. Conclusion: Although MCP are typically assessed in tensiomyography using the NMESa that elicit peak muscle displacement, a submaximal NMESa may have a higher potential practical application to assess neuromuscular fatigue in response to repeated sprints.